Activity rhythms of the shallow-water octopuses Octopus laqueus and Abdopus aculeatus with special reference to its relation to light and tidal cycles. Issue 4 (4th July 2018) - Ikeda, Yuzuru; Yanagisawa, Ryoko
Abstract: Patterns of activity and inactivity were experimentally measured for two shallow-water octopuses,   Octopus laqueus  ( n  = 8) and  Abdopus aculeatus ( n  = 4), inhabiting the Ryukyu Archipelago. Octopuses that were collected from the coastal waters of Okinawa Island were held in experimental tanks under controlled light conditions (L, light; D, dark; 12L:12D, LD conditions; 12D:12D, DD conditions). Behaviors of these two species were continuously recorded for 9 to 10 days. Under LD conditions,   O. laqueus  were active for 7 to 14 min during daytime and 298 to 339 min at night, and under DD conditions, for 97 to 140 min during daytime and 71 to 169 min at night.  A. aculeatus  were active for 49 to 99 min during daytime and 138 to 185 min at night under LD conditions, whereas under DD conditions, they were active for 36 to 56 min during daytime and 55 to 154 min at night. Continuous duration for activity cycles was 39 ± 7.6 h under LD conditions and 42 ± 2.6 h under DD conditions in  O. laqueus,  and 38 ± 7.4 h under LD conditions and 42 ± 2.8 h under DD conditions in  A. aculeatus . Ratios for active duration to inactive duration did not differ between LD condition and DD condition both in  O. laqueus  and  A. aculeatus .